Estudio de prefactibilidad para la instalación de una planta procesadora de pulpa congelada de maracuyá (Passiflora edulis) - Romero Rodríguez, Paola Alexandra (2020)
This pre-feasibility study seeks to determine the commercial, technical, economic, financial and social viability of a frozen passion fruit (Passiflora edulis) pulp processing plant that facilitates the preparation of soft drinks or drinks at home.